Got Invasives? Get Help! - Benjamin Koubek; Chris Demers (EDIS)
FOR-223, a 2-page fact sheet by Benjamin Koubek and Chris Demers, describes the FloridaInvasives.org website and how it can help landowners and land managers locate valuable technical and financial assistance programs to prevent or control invasive exotic species problems. Published by the UF School of Forest Resources and Conservation, June 2009.